A escolha de parceiro (a) ideal por hetero e homossexuais: uma leitura a partir dos valores e traços de personalidade - Gomes, Ana Isabel Araújo Silva de Brito (2011)
This dissertation aimed to know the extent to which human values and personality traits correlate themselves with the desirable attributes of an ideal partner for heterosexuals and homosexuals. Participants were 372 people from the general population in Joao Pessoa (PB). Of these, 178 were female (47.9%), divided into heterosexuals (n = 100) and homosexuals (n = 78), and 194 males (52.1%), divided into heterosexuals (n = 105) and homosexuals (n = 89). Their ages ranged from 18 to 52 years (m = 25.0, sd = 6.38), mostly single (73.7%) and undergraduate students (52.7%); half of them indicated to be involved in a stable relationship. They answered the Basic Values Survey (BVS), the Big Five Inventory (BFI), the Attributes of Ideal Partner Scale (AIPS), and demographic questions. Results indicated that values were correlated in a theoretically consistent way with the attributes of an ideal partner, being more prevalent than personality traits. Moreover, it was shown that men and women differ in the importance they given to these attributes, with the former prioritizing the athletic dimension, and the later the affectionate dimension. Scarce variance was observed in this pattern with respect to homosexual respondents. Finally, the hierarchical model of values  personality traits  desirable attributes was adequate. These findings were discussed from an evolutionary perspective, taking into account the contribution of the functionalist theory of human values and model of the big five personality traits to explain the variability in the importance given to the desirable attributes when choosing an ideal partner.